A Multilevel Analysis of Professional Conflicts in Health Care Teams: Insight for Future Training. (November 2017) - Bochatay, Naike; Bajwa, Nadia M.; Cullati, Stéphane; Muller-Juge, Virginie; Blondon, Katherine S.; Junod Perron, Noëlle; Maître, Fabienne; Chopard, Pierre; Vu, Nu Viet; Kim, Sara; Savoldelli, Georges L.; Hudelson, Patricia; et al.
Abstract : Purpose: Without a proper understanding of conflict between health care professionals, designing effective conflict management training programs for trainees that reflect the complexity of the clinical working environment is difficult. To better inform the development of conflict management training, this study sought to explore health care professionals' experiences of conflicts and their characteristics. Method: Between 2014 and early 2016, 82 semistructured interviews were conducted with health care professionals directly involved in first-line patient care in four departments of the University Hospitals of Geneva. These professionals included residents, fellows, certified nursing assistants, nurses, and nurse supervisors. All interviews were transcribed verbatim, and conventional content analysis was used to derive conflict characteristics. Results: Six conflict sources were identified. Among these sources, disagreements on patient care tended to be the primary trigger of conflict, whereas sources related to communication contributed to conflict escalation without directly triggering conflict. A framework of workplace conflict that integrates its multidimensional and cyclical nature was subsequently developed. This framework suggests that conflict consequences and responses are interrelated, and might generate further tensions that could affect health care professionals, teams, and organizations, as well as patient care. Findings also indicated that supervisors' responses to contentious situations often failed to meet health care professionals' expectations. Conclusions: Understanding conflicts between health care professionals involves several interrelated dimensions, such as sources, consequences, and responses to conflict. There is a need to strengthen health care professionals' ability to identify and respond to conflict and to further develop conflict management programs for clinical supervisors.